Testing the Existence of Natural Resource Curse in Indonesia: The Role of Financial Development - Ridena, Sedwivia; Nurarifin, Nurarifin; Hermawan, Wawan; Komarulzaman, Ahmad (Jurnal Ekonomi & Studi Pembangunan, 2021)
Natural resources may become a blessing that can contribute to societies’ welfare increases. Yet natural resource abundance could also become a curse for countries’ economic development. Numerous studies have investigated the relationship between natural resources and economic performance. However, the results remain ambiguous and have no consensus in the literature. In specific, most literature focused only on testing the curse’s existence, while studies that involve the role of financial development in mediating the nexus remain scarce. To the best of our knowledge, this is a pioneer study in a developing country endowed by natural resources. Using panel data of 33 provinces from 2012 to 2018, this study implements the Generalized Method of Moments (GMM) technique to examine the existence of the natural resource curse and scrutinize the role of financial development in mitigating the curse. Results show that Indonesia potentially experiences a natural resource curse. Nonetheless, the negative effect of natural resources on economic growth could be mitigated by enhancing the role of financial development to reach a certain threshold over economic output. This study recommends policymakers to not only increase financial development across the provinces but also pay more serious attention to other factors causing the natural resource curse in Indonesia.